Macroscopic visible core length can predict the histological sample quantity in endoscopic ultrasound‐guided tissue acquisition: Multicenter prospective study. Issue 3 (14th September 2021) - Kaneko, Junichi; Ishiwatari, Hirotoshi; Sasaki, Keiko; Yasuda, Ichiro; Takahashi, Kosuke; Imura, Johji; Iwashita, Takuji; Uemura, Shinya; Hatano, Yuichiro; Miyazaki, Tatsuhiko; Satoh, Tatsunori; Sato, Junya; et al.
Abstract : Objectives: Measurement of the macroscopic visible core (MVC) length during macroscopic on‐site quality evaluation (MOSE) may allow estimation of sample adequacy for next‐generation sequencing (NGS), and prediction of correct diagnosis in endoscopic ultrasound‐guided tissue acquisition (EUS‐TA) of pancreatic masses. Methods: This multicenter prospective study included consecutive patients who underwent EUS‐TA for pancreatic masses using a 22‐G Franseen needle. MVC length and pathological samples obtained from two needle passes were analyzed on a per‐pass basis. Outcome measures included respective correlations of MVC length with histological sample quantity and diagnostic yields. Results: The analysis included 204 passes from 102 EUS‐TAs. MVC length correlated positively with histological sample quantity ( P  < 0.01). On the receiver operating characteristic curve for MVC length, the cut‐off value and area under the curve for obtaining a candidate sample for NGS were 30 mm and 0.74 (95% confidence interval [CI] 0.65–0.83), respectively. On multivariate analysis, MVC length ≥30 mm was a significant factor affecting suitability for NGS (odds ratio 6.19; 95% CI 2.72–14.10). Histologic diagnostic yield correlated positively with MVC length ( P  = 0.01); however, there was no positive correlation between MVC length and overall (histology plus cytology) diagnostic yield. Conclusions: Measuring MVC length to predict histological sample quantity on MOSE may be of clinical significance during EUS‐TA using a 22‐G Franseen needle. It may be an effective method, particularly while submitting samples for NGS. Registration: University Hospital Medical Information Network Trials Registry (UMIN000036528).